Evaluation of porous friction courses with highly modified asphalts to reduce raveling (2018)
"Porous asphalt courses (PFC) are mixtures with a high air void content (i.e. 18-20% air void content) that are placed as thin layers over the surface of conventional flexible asphalt pavements, with the purpose of improving environmental aspects and enhancing road safety conditions. A main challenge associated to these mixtures is known as ?raveling? which is the dislodgement of particles from the surface of the structure that reduces their durability. For this reason, polymer modified asphalt (PMA) and asphalt rubber have been used in the fabrication of these mixtures to increase theirs service lives. However, even with the use of these binders PFC mixtures continue presenting short service periods (i.e. usually between 8-12 years). For this reason, polymer highly modified asphalts, also known as HiMA are an alternative to increase the durability of this type of mixtures. The main objectives of this work are to characterize and compare in terms of the asphalt, the mixture and through numerical modeling the durability of PFC mixtures fabricated with HiMA and PMA. The results infer that mixtures with HiMA have an overall better mechanical performance in the long term than mixtures with PMA and, therefore, are expected to present longer disabilities."--Tomado del Formato de Documento de Grado.